The Effects of Physical Exercise Intensity Towards Heart Rate Deflection Point - Umar; Alnedral; Bakhtiar, Syahrial; Syarli Lesmana, Heru (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to analyze the effect of physical exercise with various types of exercise intensity on heart rate deflection points. The point of heart rate deflection is the meeting between the number of minute heartbeats and the number of lactic acid levels of 4 mmol/L. A lactic acid level of 4 mmol/L is a point of fatigue felt by someone during physical activity. This type of research is quasi-experimental with a population of UNP FIK Sport Coaching Department students. The sample involved 30 students of UNP FIK Sport Coaching enrolled in 2016/2017. The treatment is in the form of physical exercise with the ergo cycle at the specified intensity (70%-75%, 80%-85%, and 90%-95%). To monitor the intensity of exercise using the pulse meter (pulsoximeter-beurer). The instrument measures lactic acid levels using the lactate analyzer The Accutrend Plus brand. Data analysis using a t-test at a α 0.05 significance level. The results of the study show that 1. The intensity of 70%-75% does not affect the shift of the deflection point (ρ > α = 0.05); 2. The intensity of 80%-85% affects the shifting of the deflection point (ρ < α = 0.05); and 3. intensity of 90%-95% has an effect towards shifting the deflection point (ρ < α = 0.05), with the conclusion that physical exercise with an intensity above 80% can cause a shift in the heart rate deflection point.